The correlation between demographic profile and students response to financial problems and financial stress - Dela Cruz, Paul Christian., Espiritu, Mary Joyce., Laosantos, Jennica T., Liwanag, Maria Gracila S., Risch, Clyde Devon., Romasanta, Maryjean 4 0 16; 5
ABSTRACT: This study aims to investigate The Correlation Between Demographic Profile and Students Response to Financial Problems and Financial Stress among third-year students in the College of Business Administration at Pamantasan ng Lungsod ng Maynila. Through a comprehensive analysis, the research uncovers how individual characteristics, such as age, gender, program, supporting system, and working student status, influence students' coping mechanisms and reactions to financial challenges. By employing the IPO framework, the study scrutinizes the impact of these demographic elements on students' financial stress experiences, shedding light on the interconnectedness between demographic factors and stressors, emphasizing the need for tailored interventions to alleviate financial pressures and enhance students' overall well-being and academic performance. Furthermore, the research contributes significantly to the theoretical understanding of the complex interplay between demographic profiles, financial management practices, and mental health outcomes among college students. By integrating theoretical frameworks like Compassion Focused Therapy (CFT) and Cognitive Behavioral Therapy (CBT), the study enriches the existing literature by providing insights into how mental health factors interact with financial behaviors within the context of college students' financial management practices. The practical implications of the study underscore the importance of addressing financial stress among students, highlighting the necessity for educational institutions to develop targeted support systems and interventions that consider students' diverse demographic characteristics to effectively manage stress and enhance their academic experience. The study's findings offer valuable insights into the complex relationship between demographic profiles, financial management practices, and mental health outcomes, providing a foundation for tailored support services to improve the well-being and academic performance of Financial Management students. The research highlights the need for future studies to address broader demographics, longitudinal designs, and additional factors influencing student financial stress. Keywords: Correlation, Demographic, Profile, Students, Financial Stress, Financial Problem
Business Research: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2